Activation of p53-dependent/-independent pathways of apoptotic cell death by chelerythrine in a murine T cell lymphoma. Issue 6 (June 2015) - Kumar, Sanjay; Tomar, Munendra Singh; Acharya, Arbind
Abstract The p53 tumor suppressor protein has been implicated as an activator of apoptosis. In order to investigate the effect of chelerythrine and staurosporine on the activation of p53-dependent/-independent pathways of Dalton lymphoma (DL) cell death, cells were treated with chelerythrine and staurosporine for 1 h, 3 h and 6 h, respectively. It was found that treatment with chelerythrine and staurosporine increased the expression of total-p53/phospho-53 (ser-15) significantly at protein and mRNA levels, which resulted in activation of the p53-dependent apoptotic pathway in DL cells. In addition, increased activities of cyt-c, caspase-9 and caspase-3 and degradation of DNA into fragments confirmed activation of the p53-independent apoptotic pathway in p53 knockdown RNAi-DL cells. In brief, the present study demonstrated activation of p53-dependent/-independent apoptotic pathways in DL cells. Therefore, targeting of p53-dependent/-independent apoptotic pathways may lead to the possibility of designing and developing better therapeutic regimens to treat DL and other human cancers.